Occurrence, infectivity and molecular characterization of hosta virus X in North-east China. Issue 4 (1st October 2020) - Song, Shuang; Cui, Jie; Lei, Gui-Jie; Chen, Yu-Fei; Yang, Ming-Xiu; Li, Zheng-Nan; Zhang, Jun-Hua
Abstract: Hosta virus X (HVX) is the most economically significant virus infecting hosta ( Hosta spp.) plants worldwide, and has been reported from North America, Europe, Asia and Oceania. In May 2019, various viral-like disease symptoms were observed on hosta plants in a park in Harbin City in North-east China, and infection by HVX was confirmed by small RNA sequencing, RT-PCR and electron microscopy. The infectivity of HVX on Hosta ensata, a native species in North-east China, was confirmed by mechanical inoculation. We determined the complete genome sequence of an isolate of the virus, which revealed a high level of sequence similarity with other HVX genome sequences published to date. Phylogenetic analysis of HVX with other potexviruses based on the complete sequences revealed that all four HVX entries clustered to a single clade, which was most closely related to cassava common mosaic virus (CsCMV), hydrangea ringspot virus (HdRSV), plantago asiatica mosaic virus (PlAMV) and tulip virus X (TVX). Two potential recombination events were detected among the four HVX isolates. This work not only reports the complete genome sequence of an HVX isolate in North-east China for the first time, but also suggests the need to prevent further spread of this virus in the region.